How to solve this simultaneous linear equation by elimination method

How to solve this simultaneous linear equation by elimination method 6 x—3y= 3x—1 = 2x — y. Hint. x—3y = 3x—1 = 2x —y x—3y = 3x — 1, 3x — 1 = 2x— y.

Dear student
We havex-3y=3x-1=2x-ySo, x-3y=3x-1,3x-1= 2x-yConsider x-3y=3x-1x-3y-3x+1=0-2x-3y+1=02x+3y-1=02x+3y=1  ...1Consider  3x-1= 2x-yx+y=1  ..2Multiply equation 2  by 2 , we get2x+2y=2 ..3Subtract  equation 3 from 1 we get2x+3y-2x-2y=1-2y=-1 x=2
Regards

  • 0
What are you looking for?